A New Monitor to Measure Dermal Blood Flow in Critically Ill Patients: A Preliminary Study. (22nd April 2013) - Cohen, Jonathan; Skoletsky, Ilya; Chen, Rina; Weiss, Daniel; Singer, Pierre
Abstract : Background . Conditions of reduced perfusion are characterized by redistribution of blood flow away from the skin to more vital organs. Objectives . To assess the efficacy of a noninvasive, dermal blood flow (DBF) monitor in detecting changes in perfusion in critically ill patients. Methods . Eleven adult, critically ill patients in a general ICU were studied. DBF, finger plethysmography, and invasive mean arterial pressure (MAP) were recorded over an 8-hour period. DBF was measured using the DermaFlow DBF monitor via a skin probe placed on the anterior chest wall. Sensitivity was evaluated by visual inspection during active states, either induced, for example, fluid administration, or spontaneous, for example, altered hemodynamics, while specificity was evaluated during stable states. Data are expressed in terms of standard deviation of the difference (SDD) between the MAP and each of the tested methods. Results . The DBF detected all true changes detected by MAP while plethysmography detected fewer of these events. Based on SDD, the specificity of the DBF was found to be better than that of plethysmography and close in value to the MAP. Conclusions . This preliminary study suggests that the DBF monitor may be a useful noninvasive method for detecting changes in perfusion in critically ill patients.